Prevalence of Aflatoxin M1 (AFM1) in Fresh Cow Milk Produced in Chattogram, Bangladesh - Mohammad Shaokat Ali; Shamima Ahmed; Mohammad Sharif Uddin; Chaudhry Ahmed Shabbir; Suvanker Saha; Shamsul Morshed (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to examine the prevalence of AFM1 contamination across different areas of Chattogram, Bangladesh, and to assess the level of AFM1 in raw milk samples from various dairy farms. A cross-sectional study was conducted to assess the farming standards of three different Chattogram neighborhoods—Bakalia, Khulshi, and Pahartali—and to ascertain the amount of AFM1 in milk. In the study location, 30 commercial dairy farms were randomly chosen, and data on farming methods, milk production techniques, and knowledge of aflatoxin contamination were gathered. Using the enzyme-linked immunosorbent assay (ELISA) method, collected milk samples (n = 90) were examined for the presence of AFM1. The farms produced 71.67±14.71 liters of milk on average every day, which was primarily supplied to dairy processing plants. For feeding the cows, all farms used concentrates and forage.  The mean concentration of AFM1 in milk samples collected from Bakalia was higher (190.00±120.87 ng/L) than that in milk samples collected from the Khulshi (108.44±66.19 ng/L) and Pahartali (189.25±160.78 ng/L). The overall prevalence of AFM1 was 43% (N=39) of the total examined samples. A total of 69% (N=27) and 5% (N=2) of AFM1 positive samples exceeded the European Union Regulation (50 ng/L) and BSTI/BFSA regulations (500 ng/L) respectively. There was a significant difference in the occurrence of AFM1 in Bakalia regarding Khulshi and Pahartali. This research will aid in measuring the AFM1 content in raw milk and helping to address public health issues.